Toward a Framework for Language MOOCs and Mobile Assisted Language Learning - Read, Timothy (2020)
In this article a proposal is presented for a theoretical framework that could provide the structure and coherence needed for the development of effective LMOOCs (Language MOOCs) and MALL (Mobile Assisted Language Learning) apps in a systematic way that would facilitate online second language learning. The framework is argued to be appropriate for language teaching and learning since it could be used for the elaboration of online courses such as LMOOCs and syllabi and didactic materials for MALL apps, regardless of the number of students. It has been refined during the process of designing and developing a Professional English LMOOC and the examples provided here are from that course. The framework is built upon the CEFR (The Common European Framework of Reference for Languages: Learning, Teaching, Assessment) since it offers a way to structure the knowledge and skills required in second language learning in a way which is coherent with the constructivist paradigm, following widely accepted European recommendations. It has been adopted because it provides a notional-functional classification of language use and learning (“elegantly” capturing the vastness and complexity of languages and their functional nature), and it is the first general attempt to produce a taxonomy of the elements that intervene in language use and learning, enabling comparable syllabi to be created for all European languages.